Determining frequency of genes of CTX‑M and CTX‑M‑15 of producing Enterobacteriaceae of isolated extended‑spectrum beta‑lactamases from clinical samples of patients referred to training hospitals of Medical Sciences University, Khorramabad, Iran - Mosavian, Seyed Mojtaba; Rezvani‑Rad, Azam (International Journal of Pharmaceutical Investigation)
Objective: The purpose of conducting this research was evaluation of the frequency of extended‑spectrum beta‑lactamases (ESBLs) in separated Enterobacteriaceae isolates from clinical samples in Khorramabad city and determination of their antimicrobial resistance pattern. Materials and Methods: In this study, 240 isolates belonging to Enterobacteriaceae family were collected in time duration between March and June in 2014. The isolates were identified by standard biochemical tests. Producing isolates of enzymes of ESBLs were identified by combined disc method and based on the Clinical and Laboratory Standards Institute criterion, and then, frequency of genes of blaCTX‑M and blaCTX‑M‑15 in positive phenotypic isolates was determined using polymerase chain reaction method. Results: In the present research, the most frequency was, respectively, belonged to Escherichia coli with 76%, Klebsiella pneumoniae ‑ 16.2%, Citrobacter freundii ‑ 5.4%, Proteus mirabilis ‑ 1.6%, and Enterobacter ‑ 0.83%. The obtained results from determining the antibiotic sensitivity pattern in the separated isolates showed that the maximum resistance of different isolates was related to antibiotics of ampicillin 88% while the minimum antibiotic resistance of isolates was related to the amikacin antibiotic with resistance value of 2.5%. The obtained results from the combined disc phenotypic method in the present research showed that from 240 Enterobacteriaceae isolates, 59% was generators of ESBLs. In addition, 85% of positive phenotype Enterobacteriacea had genes of blaCTX‑M‑15 and blaCTX‑M that totally formed 50.4% of all separated bacteria from the clinical samples. Conclusion: The obtained results from the present research showed that the prevalence of ESBL enzymes and antibiotic resistance to ESBLs is high among the separated Enterobacteriaceae isolates from the clinical samples in Khorramabad city. Hence, policies of prescription of antibiotics and infection control in hospitals should be reviewed.
Keywords: CTX‑M; CTX‑M‑15; Enterobactericeae; extended‑spectrum beta‑lactamase; Khorramabad; Iran; polymerase chain reaction